Determinants of Students’ Learning Satisfaction in E-learning English Class in Chongqing University, China - Dandan, Sun (Scholar: Human Sciences, 2025)
Purpose: In a public university in Chongqing, China, this study attempts to evaluate the critical factors that have a major impact on students learning satisfaction in an online English course. Key variables are course content quality, perceived ease of use, perceived usefulness, confirmation, flow experience, and students’ e-learning satisfaction. Research design, data, and methodology: 304 students in the seven journalism college classes were the subject of an investigation by the researcher using a quantitative approach and questionnaires. Convenience, quota, and judgmental sampling techniques are utilized. Before the data collection, the item-objective congruence index (IOC) and a pilot test (n=80) were carried out. Intervention Design Implementation (IDI) was conducted among 30 participants. Results: The results confirm that all the factors, such as course content quality, perceived ease of use, usefulness, flow experience, and confirmation, significantly impact students’ e-learning satisfaction. Conclusions: Administrators and faculty at public universities should focus on improving factors that affect students’ satisfaction with e-learning. By improving the quality of course content, making it easier to use and more attractive, increasing its usefulness, providing confirmation, and enhancing the flow experience, they can enhance students’ satisfaction with e-learning in English classes.